The Viral Phenomenon of Ventela Shoes in East Java: Local Brand Strategy Through the Power of Digital Marketing - Latif , Nashrudin; Suharyanto; Afkar, Taudlikhul (Indonesian Journal for Entrepreneurial Review, 2026)
The strategies of Influencer Marketing, Electronic Word of Mouth (E-WOM), and focus on Product Quality have enabled the Ventela shoe brand to compete with other Sneakers shoe products, such as Nike, Adidas and Converse, in East Java. The dynamics of local versus international brand competition are changing consumer behavior in the global market. A quantitative approach was used in this study, with regression testing and accidental sampling techniques involving 180 respondents in East Java. The results show that Influencer Marketing strategy is the dominant factor influencing purchase decisions, followed by Product Quality and E-WOM, where all three are proven to have a significant effect on consumer purchase intention for Ventela brand shoes in East Java. The phenomenon of Ventela brand popularity has changed the paradigm of consumer behavior, where the social media era influences purchasing decisions in the teenage and young generation segments in East Java